2019
DOI: 10.1111/ssm.12336
|View full text |Cite
|
Sign up to set email alerts
|

How well aligned are common core textbooks to students’ development in area measurement?

Abstract: Among dozens of factors that influence mathematics teaching in the elementary classroom, textbooks endure as a significant contributor to the conversation. While teachers have many considerations while lesson planning, the textbook often forms an important launch point in determining what to include in lessons and how to do so. It follows that discrepancies between textbooks and research-recommended pathways for learning may lead to concerns or issues with pacing in the classroom. To explore this idea further,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…LPs have shown an increased visibility in the field, including being an essential element in the NRC's () Framework document as well as informing the NGSS itself. However, just like Hong et al () found for mathematics and learning trajectories, misinterpretation or inattention could result in disordered sequence of content and practices that is inconsistent with the proposed trajectories. Yet for science, despite the widespread discussion about LPs, they are recognized as tentative, hypothetical, and requiring ongoing empirical validation.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…LPs have shown an increased visibility in the field, including being an essential element in the NRC's () Framework document as well as informing the NGSS itself. However, just like Hong et al () found for mathematics and learning trajectories, misinterpretation or inattention could result in disordered sequence of content and practices that is inconsistent with the proposed trajectories. Yet for science, despite the widespread discussion about LPs, they are recognized as tentative, hypothetical, and requiring ongoing empirical validation.…”
Section: Discussionmentioning
confidence: 86%
“…Should we compare everything directly to NGSS, to an alternative framework derived directly from the NRC Framework , or to some other framework such as PISA, TIMSS, or the NAEP documents? Comparison frameworks could be made on an ad hoc basis using established content and cognitive distinctions (Liu & Fulmer, ), generated by analysis of alternative frameworks with international visibility (Alonzo, ; Khaliqi, ), produced with input from experts in policy and research (Porter et al, ), or developed by reinterpreting standards to emphasize other characteristics (Hong et al, , Troia et al, ). Even if a researcher opts to compare against NGSS directly, should they compare with respect to PEs, the three dimensions associated with the PEs, or some combination of dimensions?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hong et al. (2019) examined math textbooks identified as being aligned with the CCSSM in comparison to the research literature for a particular topic, area measurement. They reported substantial misalignments, especially in the early grades.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(1986) seems to imply that many U.S. students are now expected to solve a wider variety of problem types than they were when Stigler et al performed their analysis of first‐grade textbooks. Although curriculum standards influence the textbooks and other instructional resources, and scholars agree that textbooks continue to play an important role in determining the enacted curriculum, the degree of alignment between the official curriculum and the instructional materials and other components of the enacted curriculum can vary (Hong et al., 2019; Polikoff, 2015; Remillard et al., 2014; Remillard & Heck, 2014; Tran, 2016). Comparing contemporary science textbooks with those of the 1980s, for example, Groves (2016) found that little had changed.…”
Section: Introductionmentioning
confidence: 99%